Jeronim Bartučević, Hortenzije Bartučević, Sabo Bobaljević Mišetić, Gabrijel Crijević, Andrija Čubranović, Nikola Dimitrović, Stijepo Đurđević, Marin Krističević, Ivan Krizmanić, Đuro Matijašević, Ivan Mršić, Jerolim Vidulić, Andrija Zlatar - Bogdan, Tomislav (2000)
.
Projekt MZOS
HRV